Central Motor Conduction Time and Diffusion Tensor Imaging metrics in children with complex motor disorders. Issue 1 (January 2015) - Lumsden, Daniel E.; McClelland, Verity; Ashmore, Jonathan; Charles-Edwards, Geoffrey; Mills, Kerry; Lin, Jean-Pierre
Highlights Both measurement of Central Motor Conduction Time (CMCT) and Diffusion Weighted Imaging (DWI) may aid with the clinical assessment of children and young people with complex motor disorders. Diffusion Tensor Imaging (DTI) metrics in a group of children with complex motor disorders did not correlate with CMCT, nor were group wise differences in DTI metrics identified when children with normal and abnormal CMCT where compared. Children and young people with acquired dystonia were frequently found to have normal CMCT values.